Outcomes of adverse analytical findings in individual and team sports - Aguilar-Navarro, Millán; Baltazar-Martins, Gabriel; Salinero, Juan José; Muñoz-Guerra, Jesús; Plata, María del Mar; Lara, Beatriz; Del Coso, Juan (Bioanalysis, 2021)
The aim of this investigation was to describe the outcomes of the adverse analytical findings in different Olympic sports. The data included were gathered from the World Anti-Doping Agency Anti-doping Rule Violations Reports (2013–2017). Weightlifting (78.1 ± 9.4%) wrestling (73.2 ± 18.5%) and volleyball (68.3 ± 18.7%) were the sports with the highest proportion of cases that ended in an antidoping sanction. Gymnastics (45.1 ± 10.1%), triathlon (32.6 ± 11.9%) and shooting (29.9 ± 14.1%) were the sports with a higher frequency of cases that were not sanctioned due to medical reasons. Gymnastics (22.4 ± 18.4%), boxing (23.2 ± 16.0%) and taekwondo (17.3.1 ± 16.4%) presented the highest proportion of cases that are still pending resolution. The proportion of cases that ended in no sanction was higher in fencing (26.2 ± 22.7%), skating (23.6 ± 35.1%) and tennis (18.6 ± 26.5%). These results indicate that the sanctions derived from antidoping rule violations were not uniform in all sports disciplines.